THE EFFECT OF COMMUNITY SATISFACTION ON EMPLOYEE PERFORMANCE IN CICAHEUM VILLAGE BANDUNG: PENGARUH KEPUASAN MASYARAKAT TERHADAP KINERJA PEGAWAI DI KELURAHAN CICAHEUM KOTA BANDUNG - Iqbal Kamaludin; Iin Surtiah; Sunandie Eko Ginanjar (Journal of Public Administration, 2022)
The level of Human Resources (HR) in government and private institutions can be seen from the performance of employees in providing effective and efficient services to the community. Employee performance is the result of work (work achievements) in quantity and quality that has been achieved by an employee in carrying out his duties in accordance with the responsibilities that have been given to him. Public service in kelurahan is a government function in carrying out and providing basic rights that are understood by all components of society as the right to be able to enjoy a dignified life. Therefore, employee performance greatly influences the quality of service in government, so this study analyzes employee performance on community satisfaction in the urban village of Bandung. The research method used is research using quantitative research types with quantitative descriptive research types. The results of the research produced are that employee performance greatly influences the quality of services carried out in the Cicaheum Village, Bandung City.